Effects of harvest ripeness on storage quality of tomato fruits - hua-ling, Zhang; Xiao-yi, Huang; Hai-ying, Wang; Xiao-ke, Jia; Qin-ru, Song; Ting, Chen; Zhi-rong, Chen (Emirates Journal of Food and Agriculture, 2023)
For studying the different recovery maturity influence on tomato postharvest storage quality, in different harvest maturity tomato (green ripe period, color-changing period, red period) as experiment material, put it in 3℃ and 28℃temperature storage, and the determination of three different harvest maturity tomato in weightlessness rate, decay rate in the process of storage, reducing sugar content, titratable acid content, lycopene content and the content of ascorbic acid and so on six indicators, according to the fuzzy weight methods to establish comprehensive evaluation index weights, determine the harvest maturity of science. The results showed that under two different temperature environments, the highest comprehensive evaluation index of tomato was 0.6644 and the storage quality was the best. The comprehensive evaluation index of tomatoes harvested in the color-changing period was 0.4709, which was more suitable for storage at 3℃. The comprehensive evaluation index of tomatoes harvested in green ripening period was 0.3919, and the storage quality was relatively poor. Key words: Tomato ；Ripeness； Effect of storage； Quality; Fuzzy weight methods